2023
DOI: 10.1007/s00284-022-03166-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Interference of Culture Filtrates of Endophytic Bacteria Associated with Nerium oleander Leaf Against Seed Germination of the Invasive Noxious Weed Cenchrus echinatus

Abstract: Weeds cause destructive agricultural losses, so weed control is an urgent challenge facing agriculture. The extensive use of synthetic chemical herbicides has detrimental environmental impacts and promotes the emergence of resistant species. Therefore, in this study we tried to find a new natural weed control that can ensure biosafety and eco-sustainability. The phytotoxic potential of culture filtrates of the endophytes Bacillus inaquosorum NL1 and Bacillus safensis NL2 isolated from Nerium oleander leaf agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This finding agreed with previous studies which reported the isolation of Bacillus spp. from different plants grown in Aswan [ 23 25 ].
Fig.1 The phylogenetic relationship among the isolates Camph.1, Camph.2, Camph.3, and the closely related species from the NCBI database using the neighbor-joining method in MEGA X10.1.7 software
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding agreed with previous studies which reported the isolation of Bacillus spp. from different plants grown in Aswan [ 23 25 ].
Fig.1 The phylogenetic relationship among the isolates Camph.1, Camph.2, Camph.3, and the closely related species from the NCBI database using the neighbor-joining method in MEGA X10.1.7 software
…”
Section: Resultsmentioning
confidence: 99%
“…This finding agreed with previous studies which reported the isolation of Bacillus spp. from different plants grown in Aswan [23][24][25].…”
Section: Isolation and Identification Of Endophytic Bacteriamentioning
confidence: 99%